Design discourse in Abrahamic traditions : history, metaphysics, and science - Kojonen, Erkki V. R.; Malik, Shoaib Ahmed (New York, NY : Routledge, 2025)
"Design Discourse in Abrahamic Traditions reconnects discussion of design arguments to its Jewish, Christian, and Muslim history. The ancient idea that there is evidence of purpose in nature remains one of the most debated topics in science and religion, but also one with great potential for inter-religious and interdisciplinary dialogue. This volume revitalizes current discussion by retrieving perspectives from the Abrahamic history of design arguments and engaging them with contemporary ideas. Beginning with the encounter ancient philosophy and creation beliefs, the book proceeds to delve deep into issues ranging from the nature of theological and teleological language to the implications of evolution and evil. This rich exploration showcases how, far from being irrelevant in a post-Humean, post-Darwinian world, design arguments continue to merit both popular-level and academic attention. The volume will be of particular interest to scholars working at the intersection of science and religion, philosophers of religion, and theologians"--
Keywords: Religion and science; Intelligent design (Teleology); Abrahamic religions; RELIGION / Philosophy; RELIGION / Theology; RELIGION / Religion & Science